The synthesis and biology of iminosugars and their precursors - Ayers, B; Benjamin Ayers (2014)
Iminosugars are carbohydrate mimics, where the endocyclic ring oxygen has been replaced by nitrogen. This substitution affords these compounds their inhibitory activity towards sugar-processing enzymes (glycosidases) and, as a consequence, their chemotherapeutic potential in the treatment of a broad range of diseases. Several iminosugars are currently in clinical trials or have entered the market as approved drugs. This has consequently led to increasing levels of research into their synthesis and application, both in terms of the development of efficient methodology to access naturally occurring examples, and also to elaborate novel scaffolds. The presence of multiple chiral centres within iminosugars provides a considerable challenge in accessing these targets by asymmetric means, whereas carbohydrates pose a more attractive chiral pool. As such the majority of literature methods have employed this latter method. The focus of the thesis is on the elaboration of robust methodologies to access both naturally occurring and novel iminosugars, and their precursors, from readily available carbohydrate starting materials. Chapter 1 presents an introduction to iminosugars, including an overview of glycosidase inhibition by this class of sugar-mimic, their historical medical usage and the basis for their potential employment in treating diabetes, lysosomal storage disorders (LSDs) and cancer. This chapter also gives a general review of the methods employed in the literature for the assembly of iminosugar scaffolds. Chapter 2 is concerned with the synthesis of iminosugars from the carbohydrate glucuronolactone. This versatile chiron has previously allowed for access to many homochiral targets, and in this thesis is used to access DGJNAc on a gram-scale. This iminosugar has been shown to be a potent α-N-acetylgalactosaminidase inhibitor and is potentially extremely valuable in the treatment of late-stage cancer. Both enantiomers of glucuronolactone are also utilised in the divergent synthesis of every stereoisomer of two classes of five-membered iminosugars; the pyrrolidines (including DMDP), and the proline amides. These compounds demonstrate remarkable biological activity against a panel of glycosidases and hexosaminidases, allowing for the analysis of the structure-activity relationship between these compounds and the target enzymes. Chapter 3 describes the development of a novel, one-pot methodology - a tandem Strecker reaction and iminocyclisation - for the assembly of trihydroxy piperidine α-iminonitriles from a range of unbranched and branched pentose monosaccharides. These piperidine α-iminonitriles are precursors to pipecolic acids which may also be potentially valuable targets in the treatment of cancer.